Multiletramentos e impressões sobre o uso de tecnologias digitais por professoras de língua portuguesa - JOSIANE DE JESUS REIS DE FREITAS (2022)
This study aims to investigate the perception of portuguese language teachers in their 90th year of elementary school about their use of digital information and communication technologies (Tdics) in their pedagogical dynamics. For this, we propose to analyze how the investigated teachers use digital technologies in their portuguese language classes, seeking to discuss possible relationships between this use and the pedagogy of multiliteracies in their pedagogical practice, as well as the importance of using digital technologies in language teaching especially considering the context of the covid-19 pandemic. For this, we dialogued, through semi-structured interviews, with four teachers from public and private schools in Campo Grande-MS who work in the 90th year of elementary school, starting from 12 (twelve) more general questions on the subject. Among the justifications for the investigation are the perceptions of the researcher as a teacher of primary education reinforcement, such as: access to technologies by students; use of technologies in language classes.The results point to some evidence of work with digital technologies in the perspective of the pedagogy of multiliteracies, but highlight many barriers to carrying out this type of practice, especially during the period of emergency remote teaching of the covid-19 pandemic. As the analyzes show, it is not possible to say that this type of work can only be facilitated by an adequate digital infrastructure, as difficulties and resistance to work are often also present in teaching practices from the perspective of multiliteracies. Keywords: Pedagogy of Multiliteracies. Digital Technologies. Critical Citizen